MAIN PECULIARITIES OF MUD FLOWS FACTOR FORMATION IN ABRANKA RIVER BASIN - IVANIK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Factors of the mud flow formation of Abranka river basin (Volovetskiy region of Zakarpatskaya area) have been determined and analyzed. The main parameters of mud flow process and their critical values have been defined on the base of influence on engineering installations. This data can be used in the calculation-analytical module of the assessment of the mud flow influence on the nature-technical systems.